2009
DOI: 10.2172/974987
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Absenteeism and Promoting Resilience Among Health Care Workers In Biological Emergencies

Abstract: Executive SummarySince the terrorist attacks of September 11, 2001, and the 2003 severe acute respiratory syndrome epidemic, homeland security and emergency response communities have increasingly focused on planning for disaster medical surge capacity-the capacity of the health care system to respond to a large influx of patients after a disaster. The ability to ensure adequate numbers of medical staff represents a crucial part of the medical response to any disaster. However, healthcare worker absenteeism dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It is important for healthcare facilities to reduce barriers for healthcare personnel reporting to work and ensure adequate resourcing during times of increased care demand. An extensive qualitative review of healthcare organizations conducted by the U.S. Department of Energy revealed that measures most likely to reduce fear-based absenteeism included effective early and ongoing communication by hospital leadership, ensuring adequacy of personal protective equipment, and maintaining adequate staffing to avoid overburdening healthcare personnel (42).…”
Section: Exposure and Contaminationmentioning
confidence: 99%
“…It is important for healthcare facilities to reduce barriers for healthcare personnel reporting to work and ensure adequate resourcing during times of increased care demand. An extensive qualitative review of healthcare organizations conducted by the U.S. Department of Energy revealed that measures most likely to reduce fear-based absenteeism included effective early and ongoing communication by hospital leadership, ensuring adequacy of personal protective equipment, and maintaining adequate staffing to avoid overburdening healthcare personnel (42).…”
Section: Exposure and Contaminationmentioning
confidence: 99%
“…Campbell et al Miller and WHO reports, all emphasized the importance of complying with the control and prevention guidelines [19,20]. Other cases of personnel vulnerability include "problems due to traffic and transfer and patient triage in the health center".…”
Section: Management Weaknessmentioning
confidence: 99%
“…"lack of isolation" and "environmental control". Multiple studies also mentioned availability of specific places such as isolated or quarantined parts to prevent the spread of disease and the effects of healthy people as one of the resilience aspects of self-regulation [19][20][21]. In addition, it seems that in this case, lack of risk perception at different levels in the health system and the weakness of the infrastructure caused lack of having a program for creating readiness and capacity building.…”
Section: Engineering and Environmental Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…27,37 However, other studies reported negative attitudes, such as fear, stigmatization, [48][49][50] and refusal to care for mpox patients. 51 Satisfactory attitude towards mpox was observed in less than a third (30.7%) of Lebanon healthcare workers. 40 Additionally, Nepalese healthcare workers still have a negative attitude regarding its control measures.…”
Section: Introductionmentioning
confidence: 96%